2018
DOI: 10.1306/0810171610917171
|View full text |Cite
|
Sign up to set email alerts
|

Petrophysical and mineralogical evolution of weathered crystalline basement in western Uganda: Implications for fluid transfer and storage

Abstract: The effects of weathering on the mineralogical and petro-physical properties of the western Uganda Archaean crystalline basement were investigated using outcrop samples. This study aimed to characterize a typical composite vertical weathering profile by the integration of data from samples with variable degree of alteration, ranging from fresh to completely weathered. A detailed description of samples is proposed , using different observation methods (e.g., x-ray computed tomography scanning and quantitative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 101 publications
4
18
0
Order By: Relevance
“…For easier visual interspecimen comparison of the throat size distributions we plotted the results by means of incremental curves calculated from the initial cumulative values. It has been demonstrated that if large pores are accessible by small throats, the mercury forced into the pore remains in it after the mercury pressure is decreased to atmospheric pressure (Wardlaw and McKellar, 1981;Yu and Wardlaw, 1986a, b). To take advantage of this phenomenon called trapping, the MIP was executed in three phases ( Fig.…”
Section: Mercury Injection Porosimetry (Mip)mentioning
confidence: 99%
“…For easier visual interspecimen comparison of the throat size distributions we plotted the results by means of incremental curves calculated from the initial cumulative values. It has been demonstrated that if large pores are accessible by small throats, the mercury forced into the pore remains in it after the mercury pressure is decreased to atmospheric pressure (Wardlaw and McKellar, 1981;Yu and Wardlaw, 1986a, b). To take advantage of this phenomenon called trapping, the MIP was executed in three phases ( Fig.…”
Section: Mercury Injection Porosimetry (Mip)mentioning
confidence: 99%
“…The fracture zone at 70 metres depth, consisting mainly of gently dipping fractures, is currently described at the bottom of the weathering profile corresponding to the upper fissured zone (Wyns et al, 2004). The weathering profile is described in several places to result from downward propagation of the structural and petrographic transformations along structural prediscontinuities (Jamtveit et al, 2011;Lachassagne et al, 2011;Walter et al, 2018).…”
Section: Organization Of the Facies And Structuresmentioning
confidence: 99%
“…It has been demonstrated that if large pores are accessible by small throats, the mercury forced into the pore remains in it after the mercury pressure is decreased to atmospheric pressure (Wardlaw and McKellar, 1981;Yu and Wardlaw, 1986a, b). To take advantage of this phenomenon called trapping, the MIP was executed in three phases ( Fig.…”
Section: Mercury Injection Porosimetry (Mip)mentioning
confidence: 99%